Local Structure and Dynamics in MPt(CN) 6 Prussian Blue Analogues - Harbourne, EA; Barker, H; Guéroult, Q; Cattermull, J; Nagle-Cocco, LAV; Roth, N; Evans, JSO; Keen, DA; Goodwin, AL (American Chemical Society, 2024)
We use a combination of X-ray pair distribution function (PDF) measurements, lattice dynamical calculations, and ab initio density functional theory (DFT) calculations to study the local structure and dynamics in various MPt(CN)6 Prussian blue analogues. In order to link directly the local distortions captured by the PDF with the lattice dynamics of this family, we develop and apply a new “interaction-space” PDF refinement approach. This approach yields effective harmonic force constants, from which the (experiment-derived) low-energy phonon dispersion relations can be approximated. Calculation of the corresponding Grüneisen parameters allows us to identify the key modes responsible for negative thermal expansion (NTE) as arising from correlated tilts of coordination octahedra. We compare our results against the phonon dispersion relations determined using DFT calculations, which identify the same NTE mechanism.